Meet the terminator: the phosphatase PP2A puts brakes on IRF-3 activation - Chattopadhyay, Saurabh (2014)
Cellular interferon response to microbial infection is transient; In a recently paper in Immunity, Long et al identifies PP2A phosphatase as a deactivator of phospho-IRF-3, the key transcription factor for interferon synthesis, thus providing one basis for the observed transiency.